Can the Implementation of Sharia Banks’ Roadmap Increase Their Performance? (Evidence from Indonesia 2012-2017) - Riko Hendrawan (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract. The purpose of this research is to compare the efficiency of 11 Sharia Banks in Indonesia and its impact on their performance. This study relies on the quarterly data from 2012-2017 and applied Data Envelopment Analysis to measure their performance. The result of the T-test shows that the P-value for two tail = 0.706. So based on this trend the P-value is greater than α = 0.05 (P-value> α). In the condition of P-value> α, H1 is rejected, meaning that there is no change in the value of efficiency between the period 2012-2014 and the period 2015-2017. This research shows that the efficiency of Islamic banking has not occurred during the implementation of the 2012-2017 Indonesian Sharia Banking Roadmap. Furthermore, the highest efficiency value during the period before implementation was 0.92 with an average efficiency value of 0.57. This means that during this period there was room to increase efficiency by 0.35. Meanwhile the period after implementing the highest efficiency value was 0.87 with an average efficiency value of 0.59. This means that during this period there was room to increase efficiency by 0.28. This means that during the 2012-2017 period, there was no significant difference in efficiency levels during the 2012-2014 period (before the implementation) and the 2015-2017 period (after the implementation of the Islamic banking road map). Keywords: DEA, Efficiency, Sharia Bank Abstrak. Tujuan dari penelitian ini adalah untuk membandingkan efisiensi dari 11 Bank Syariah di Indonesia dan dampaknya terhadap kinerja bank tersebut. Penelitian ini menggunakan data setiap kuartal selama tahun 2012 hingga tahun 2017 dan menggunakan Data Envelopment Analysis untuk mengukur kinerja. Hasil penelitian ini menunjukan bahwa selama implementasi Roadmap, perbankan syariah belum menunjukan kenaikan efisiensi. Sementara itu, sebelum implementasi tersebut, nilai efisiensi tertinggi perbankan syariah sebesar 0,92, sedangkan rata-rata nilai efisiensinya sebesar 0,57. Ini berarti bahwa ada ruang untuk meningkatkan level efisiensi sebesar 0,35. Sedangkan pada periode implementasi, nilai efisiensi tertingi perbankan syariah sebesar 0,87, dan ratarata nilai efisiensinya sebesar 0,59. Ini berarti ada ruang untuk meningkatkan level efisiensi sebesar 0,28. Hasil penelitian juga menunjukan bahwa, secara keseluruhan periode tahun 2012 hingga tahun 2017, hasil t-test menunjukan nilai P-value for two tail = 0.706. Ini berarti P-value> α, dan menolak H1, sehingga tidak terdapat perbedaan level efisiensi selama periode 2012-2014 (sebelum implementasi) dan periode 2015 – 2017 (setelah implementasi) Kata kunci: DEA, Efisiensi, Bank Syariah